MO065: The Association of Glomerular Neural Cell Adhesion Molecule-1 Expression with Membranous Lupus Nephritis and the Injury of Central Nervous System. (3rd May 2022) - Liu, Yang; Zhang, Mingchao; Luo, Song; Xu, Feng; Yang, Fan; Chen, Dacheng; Xia, Wen; Miao, Yiqi; Jiao, Chenfeng; Chen, Xin; Liu, Xia; Hu, Winxin
Abstract: BACKGROUND AND AIMS: Neural cell adhesion molecule-1 (NCAM-1) has been found to be associated with central nervous system (CNS) injury in patients with lupus nephritis in small case series. This study aimed to explore the relationship between glomerular NCAM-1 expression and CNS injury in patients with membranous lupus nephritis (MLN) and the influence of NCAM-1 expression on the prognosis of MLN. METHOD: 238 patients(47 class V, 132 mixed class V + III/IV, 46 class III/IV, 7 class II, 6 lupus podocytopathy) with SLE-associated CNS injury were screened from the LN cohort between 2009 and 2019. CNS injury was assessed by clinical and brain MRI. Patients without CNS injury were served as the control. The degree of electron-dense subepithelial deposits and proportion of podocyte foot process effacement (FPE) was assessed semi-quantitatively by electron microscopy. Kidney NCAM-1 was stained by immunohistochemistry. The NCAM-1 expression in patients with different classes of LN and its relationship with CNS injury was analyzed. RESULTS: In total, positive NCAM-1 staining was found in 59 of 238 (24.8%) LN patients with CNS injury. NCAM-1 positive rates were significant higher in the cases with class V (22/47, 46.8%) and mixed class (35/132, 26.5%) than those with proliferative class (2/46, 4.3%), class II (0/7) and lupus podocytopathy (0/6). NCAM-1 positive rate was significantly higher in class V (46.8% versus 13.3%, P < 0.001) and mixed class (26.5% versus 7.3%, P < 0.001) patients with CNS injury than those patients without CNS injury. Compared with NCAM-1 negative MLN (included class V and mixed class) patients with CNS injury, NCAM-1 positive MLN patients had much higher proportion of nephrotic syndrome (54.4% versus 37.2%, P = 0.03), hypoalbuminemia (66.7% versus 49.2%, P = 0.029), extensive subepithelial immune deposits (56% versus 25.5%, P = 0.009) and proportion of FPE (75.4 ± 10.2% versus 68.1 ± 16.6%, P = 0.038), and significantly lower duration of SLE (12.0 (3.0, 48.0) months versus 26.0 (4.5, 84.0) months, P = 0.046) and renal CI score (2.0 (1.0, 3.0) versus 3.0 (2.0, 4.0), P < 0.001). No significant differences were found between the NCAM-1 positive and NCAM-1 negative MLN patients in the baseline SCr level, imaging features of brain MRI, extrarenal organ involvement and long-term patient and renal outcomes. CONCLUSION: NCAM-1 is associated with MLN (including class V and mixed class) and CNS injury, and NCAM-1 positive MLN shows special clinicopathological features of renal injury, indicating that NCAM-1 positive MLN could be a subtype of MLN.